Comparison of Environmental Costs of Hospital X in 2023 and 2024 Based on Hansen and Mowen Theory - Drastyana, Serlly Frida; Prasetyorini, Anif; Indahyati, Emilya; Rizki, Muhammad Risya; Puryanti, Puryanti (Indonesian Journal Publisher, 2025)
Every hospital is required to perform waste treatment and management processes. Measurement, assessment, disclosure, and reporting are procedures required to manage waste management costs generated from hospital operations. The purpose of this study is to analyze the environmental costs of Hospital X. This research is a descriptive quantitative type. This research was conducted in August - December 2024. Primary and secondary data were collected. Environmental prevention and detection costs are lower than internal failures in 2023 and 2024. The total costs incurred in 2023 were greater than those in 2024. The data also shows that there were no expenditures related to external environmental failure costs. The largest percentage is also shown in the internal failure cost expenditure which is 1.62% in 2023 and 1.15% in 2024.